‘BAJAPUIK’ TRADITION IN THE PARIAMAN PEOPLE’S MARRIAGE IN BINJAI CITY, NORTH SUMATRA - Deliani Deliani Deliani (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2017)
This study aimed to determine the change of Bajapuik tradition in the marriage of Minang Pariaman people in Binjai city. The research was conducted using qualitative method. The findings in this study: (1) The implementation of the marriage tradition of Bajapuik Minang Pariaman took place with a number of variations and simplifications in it, (2) Changes in the structure of Minang Pariaman people at least marked by shifting structure in their kinship system from the concept of extended family to the form of nuclear family, (3) The changes that occur in the social structure of Minang Pariaman people has implications for the change of cultural values orientation in the implementation of Bajapuik tradition. In addition to the influence of the external and social culture of people of Minang Pariaman (external factors) changes in bajapuik traditions are driven by internal needs factors (internal factors). Efforts made to maintain bajapuik tradition is done by the process of fostering and development of culture and traditions of Minang Pariaman people in Binjai City. Key Words:  Bajapuik Tradition, Marriage, Pariaman People